LOCAL TOURISM LONDRINA-PR: ANALYSIS OF THE STAKEHOLDER THEORY - Cintra, Renato Fabiano; Amâncio-Vieira, Saulo Fabiano; Goncalves, Lidiane Parron; Costa, Benny Kramer (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The paper aims to identify and characterize the stakeholders of the local tourism Londrina, PR, from the perspective of public administration, based on the Theory of Stakeholder. The research used qualitative methods with descriptive purposes only and case study on the Tourist Board of Londrina Development Institute, the body responsible for the planning and management of tourism in Londrina. It is applied to the data collection, semi-structured interviews and documentary research. They were identified tourism field and the entities involved, resulting in a sample of 46 institutions (26 classified as primary stakeholder, 8 and 12 as secondary as non-stakeholder). It is noteworthy that, from quantifiable criteria, only three institutions would be out of power attribute and would fall in the category no stakeholder. Also, a considerable part should have been framed as a secondary stakeholder, as well as a minority as the primary stakeholder, but it did not.